2006
DOI: 10.1097/01.tp.0000235434.13327.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Survival Benefit of Kidney Retransplantation

Abstract: Following primary graft failure, retransplantation is associated with significantly reduced mortality rates among Canadian end-stage renal disease patients. Further study should be undertaken to assess the applicability of our findings to other patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 19 publications
2
99
0
6
Order By: Relevance
“…It has been shown using national data that retransplantation is superior to remaining on dialysis (8,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown using national data that retransplantation is superior to remaining on dialysis (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increased relative risks associated with retransplantation, patients receive a significant survival benefit as opposed to remaining on dialysis after a failed transplant (8,9). Several studies have shown that survival of a first graft is an important determinant of subsequent transplant outcome (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Diyalizde kalan hastalarla kıyaslandığında retransplantasyon yapılan grupta mortalitenin %50 azaldığı gösterilmiştir (45). USRDS veri tabanı verilerine göre graft kaybı sonrası diyalize dönen hastalarda retransplantasyon oranı %15-20'nin altındadır (46).…”
Section: Retransplantasyonunclassified
“…Diyalizde kalan hastalarla kıyaslandığında retransplantasyon yapılan grupta mortalitenin %50 azaldığı gösterilmiştir. Retransplantasyon yapılan hastaların mortalitesi yalnızca transplantasyon sonrası ilk ay içinde diyalizdeki hastalardan daha yüksektir (36). Retransplantasyon ile ilgili bir derlemede (37) en iyi sonucu alabilmek için retransplantasyon öncesinde hastanın ayrıntılı bir şekilde incelenmesi önerilmiştir.…”
Section: Retransplantasyonunclassified